Dietary calcium impairs tomato lycopene bioavailability in healthy humans. Issue 12 (10th January 2017) - Borel, Patrick; Desmarchelier, C.; Dumont, U.; Halimi, C.; Lairon, D.; Page, D.; Sébédio, J. L.; Buisson, C.; Buffière, C.; Rémond, D.
Abstract: Lycopene (LYC) bioavailability is relatively low and highly variable, because of the influence of several factors. Recent in vitro data have suggested that dietary Ca can impair LYC micellarisation, but there is no evidence whether this can lead to decreased LYC absorption efficiency in humans. Our objective was to assess whether a nutritional dose of Ca impairs dietary LYC bioavailability and to study the mechanism(s) involved. First, in a randomised, two-way cross-over study, ten healthy adults consumed either a test meal that provided 19-mg (all-E)-LYC from tomato paste or the same meal plus 500-mg calcium carbonate as a supplement. Plasma LYC concentration was measured at regular time intervals over 7 h postprandially. In a second approach, an in vitro digestion model was used to assess the effect of increasing Ca doses on LYC micellarisation and on the size and zeta potential of the mixed micelles produced during digestion of a complex food matrix. LYC bioavailability was diminished by 83 % following the addition of Ca in the test meal. In vitro, Ca affected neither LYC micellarisation nor mixed micelle size but it decreased the absolute value of their charge by 39 %. In conclusion, a nutritional dose of Ca can impair dietary LYC bioavailability in healthy humans. This inhibition could be due to the fact that Ca diminishes the electrical charge of micelles. These results call for a thorough assessment of the effects of Ca, or other divalent minerals, on the bioavailability of other carotenoids and lipophilic micronutrients.